Macroeconomic Uncertainties, Oil Subsidies, and Fiscal Sustainability in Asia - Shikha Jha; Pilipinas Quising; Shiela Camingue (Asian Development Bank (ADB), 2009)
Global oil prices have subsided relative to the peak reached in mid-2008, but compared to historical levels they remain elevated and volatile as economic uncertainties continue to unfold. The likelihood of these prices rising again soon cannot be ruled out. High oil prices can adversely affect growth, employment, external accounts, and fiscal positions of governments. An overwhelming response across Asia as international oil prices spiked in 2008 was to shield domestic consumers more than before through oil subsidies, which are inequitable, economically inefficient, and environmentally unfriendly. These subsidies add directly to the fiscal deficit and public debt, but are generally hidden, making their measurement difficult. Additionally, in combination with lower growth rates, higher spending to rev up demand across Asia is also worsening the fiscal positions of governments. This paper computes the transmission of recent global oil price movements to domestic markets and estimates oil price subsidies in a diverse group of 32 Asian economies. Using data for 18 of these countries and applying a forward-looking methodology for debt dynamics, the paper then examines the potential impact of responses to macroeconomic shocks and a possible rise in oil prices on public debt and estimates the fiscal correction needed to sustain debt at a steady-state level. Based on the findings from the empirical analysis, the paper extracts some guiding principles for fiscal policy responses to the economic shocks depending on country-specific circumstances.
hdl:11540/1799
Keywords: H24; H62; H63; H68; 330; Oil subsidies; price pass through; macroeconomic uncertainty; stimulus packages; fiscal sustainability; public debt; Asia; Ölpreis; International; Liquiditätsbeschränkung; Finanzpolitik; Nachhaltigkeit; Asien